Multi Unit Spares Inventory Control-Three Dimensional (MUSIC 3D) Approach to Inventory Management - Zaidatun Ni'mah; Yuniar Farida (Jurnal Matematika MANTIK, 2019)
Inventory control is a series of efforts that need to be done for each company to generate the maximum profit from existing inventory. In this study inventory control was conducted through the Multi-Unit Spares Inventory Control – Three Dimensional (MUSIC 3D) approach at PT Fajar Mas Murni Surabaya using three analysis, namely ABC analysis, SDE analysis, and FSN analysis. The result of ABC analysis show that category A consists of 6 items (3%) which contribute 81% to company income, category B consists of 16 items (8%) which contributes 15% to company income, while category C consists of 190 items (89%) which contribute 4% to company income. The result of SDE analysis shows that category S consists of 127 items (60% of all items), category D consists of 43 items (20% of all items), while category E consist of 42 items (20% of all items). The result of FSN analysis show that category F consists of 15% (7% of all items), category S consists of 41 items (19% of all items) and category N consists of 156 items (74% of all items).